3(x-2)+4=2(x+3)

Simple and best practice solution for 3(x-2)+4=2(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+4=2(x+3) equation:


Simplifying
3(x + -2) + 4 = 2(x + 3)

Reorder the terms:
3(-2 + x) + 4 = 2(x + 3)
(-2 * 3 + x * 3) + 4 = 2(x + 3)
(-6 + 3x) + 4 = 2(x + 3)

Reorder the terms:
-6 + 4 + 3x = 2(x + 3)

Combine like terms: -6 + 4 = -2
-2 + 3x = 2(x + 3)

Reorder the terms:
-2 + 3x = 2(3 + x)
-2 + 3x = (3 * 2 + x * 2)
-2 + 3x = (6 + 2x)

Solving
-2 + 3x = 6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-2 + 3x + -2x = 6 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-2 + 1x = 6 + 2x + -2x

Combine like terms: 2x + -2x = 0
-2 + 1x = 6 + 0
-2 + 1x = 6

Add '2' to each side of the equation.
-2 + 2 + 1x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 6 + 2
1x = 6 + 2

Combine like terms: 6 + 2 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| 16-2/3x=4 | | 18x+19x= | | 2.5+2= | | 4w=2w+4 | | -2*r^5=-512 | | 0.60x+0.05(14-x)=0.10(-70) | | 7(x+3)=7(x+14) | | n+3n=-18 | | 3m-8=2m-2 | | 18x+3=19x-1 | | 1.58x=90y | | 7-(3+4i)+6i= | | D+2=13-5 | | 90=x+97 | | 7x-(-5)-2x=5x+17 | | 2x+4y-4z=2 | | -16k=20-17k | | -5+7p=8p | | g(x)=3(1/2)^x | | 3/4-7=2 | | -p/-10-3=5 | | 4n-9+5n= | | .5x-(x+.5)=.25(k+1) | | 12x-(5x-3)=31 | | 200=-16t^2+118t+3 | | 6u=4u-10 | | 5sin^2x+3sinx-1=0 | | X/2-10=25 | | 12+6+x= | | 97+x=90 | | P/3-2=5 | | 1.58x+y=90 |

Equations solver categories